Implementasi Metode Talaqqi dan Metode Bin-Nadhar dalam Pembelajaran Ekstrakurikuler Tahfidz - Muhammad Almi Hidayat (Moderasi : Journal of Islamic Studies, 2021)
MTs Swasta Madani is one of the formal educational institutions that has a tahfidz Quran extracurricular program. Tahfidz teachers implement the talaqqi method and bin-nadhar method in tahfidz extracurricular learning. Talaqqi method and bin-nadhar method are considered easy to apply for private MTs students. The purpose of this study is explaining the application of talaqqi method and bin-nadhar method in tahfiz extracurricular activities ,explaining the obstacles faced and solution. The results of this study: The steps for applying the talaqqi method where the teacher reads the Quranic verses that will be memorized by students with the correct recitation of the rhythm of Imam Thoha Al-Junayd then followed by the students. Then it is continued by using the bin nadhar method which invites students to read verse by verse which will be memorized repeatedly until they are memorized, after that it gives time for students to memorize themselves and deposit the memorization to the teacher if they have really memorized it. Constraints: the ability of each student is different so the target of memorization is not achieved evenly, lack of support from parents who do not help their children repeat memorization at home and narrow classrooms and different types of Quran manuscripts. Solution: the teacher groups students who are not fluent in reading the Quran to take tahsin classes, invites parents to control children learning the Quran and repeat memorization at home and instruct students to use a similar Quran.